VILLAGE GOVERNMENT POLICIES IN CONSERVING THE MAPPADENDANG HARVEST PARTY IN BINUANG VILLAGE, BALUSU DISTRICT, BARRU REGENCY - Asriani (P3M Stia Al Gazali Barru and Meraja media, 2022)
[Full Paper] to pdf Copyright (c) 2022 The Visual journal